2015
DOI: 10.1016/j.drugalcdep.2015.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Within-prison drug injection among HIV-infected male prisoners in Indonesia: A highly constrained choice

Abstract: Background In Indonesia, incarceration of people who inject drugs (PWID) and access to drugs in prison potentiate within-prison drug injection (WP-DI), a preventable and extremely high-risk behavior that may contribute substantially to HIV transmission in prison and communities to which prisoners are released. Aims This mixed method study examined the prevalence, correlates, and social context of WP-DI among HIV-infected male prisoners in Indonesia. Methods 102 randomly selected HIV-infected male prisoners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 52 publications
2
41
0
4
Order By: Relevance
“…CD4 testing) would result in more timely ART initiation among those ready to start ART, lead to more appropriate medication selection, and provide crucial feedback about ART efficacy. Concerns that ART could precipitate withdrawal or be harmful if “mixed” with methadone, which although available in some Indonesian prisons may be highly stigmatized [55], could lead patients to skip doses or stop treatment [56]. Increased coordination between HIV care and addiction treatment is needed to address interactive toxicity beliefs and proactively adjust methadone dose when starting ART to prevent symptoms of withdrawal [57].…”
Section: Discussionmentioning
confidence: 99%
“…CD4 testing) would result in more timely ART initiation among those ready to start ART, lead to more appropriate medication selection, and provide crucial feedback about ART efficacy. Concerns that ART could precipitate withdrawal or be harmful if “mixed” with methadone, which although available in some Indonesian prisons may be highly stigmatized [55], could lead patients to skip doses or stop treatment [56]. Increased coordination between HIV care and addiction treatment is needed to address interactive toxicity beliefs and proactively adjust methadone dose when starting ART to prevent symptoms of withdrawal [57].…”
Section: Discussionmentioning
confidence: 99%
“…This is not only affected by social conditions (eg, incarceration, poverty) but also includes the policing practices that influence arrest and entry into the criminal justice system and the experiences within the prison environment itself, which result in the syndemic of social and medical comorbidities. The amplification of drug-related harm in prisons 1719 is best understood using the risk environment framework. 15 This conceptual model posits that individual decisions about disease prevention and treatment are rooted in structural risk such as spaces (in this case, prisons) that, while exogenous to the individual, independently contribute to risk-taking and health-seeking behaviours.…”
Section: Methodsmentioning
confidence: 99%
“…Over 90% of men surveyed in a 2015 study in Indonesia said they shared injection equipment while injecting drugs in prison, and 78% said they shared equipment with ten or more other prisoners. 203 UNODC in 2015 summarized reports from 43 UN member states that had estimated or surveyed lifetime, annual, and past-month drug use while in prison among people in custody (Figure 16). 7 A study of drug use in prison in the European Union, found that reported rates of ever having injected drugs in prisons among the countries providing data were in the range of 15–30%.…”
Section: Drug-related Incarceration and Healthmentioning
confidence: 99%